Langfristige Prognose der Einnahmeentwicklung für den Landeshaushalt des Freistaates Sachsen bis zum Jahr 2025: Gutachten im Auftrag des Sächsischen Staatsministeriums der Finanzen - Johannes Steinbrecher; Christian Thater; Marcel Thum; Oskar Krohmer (ifo Institut, Niederlassung Dresden, 2010)
This project presents a continuation of the revenue forecast of the Free State of Saxony until 2025. For sustainable regional politics, more transparency in political decision-making, and especially in the current financial and economic crisis, a continuously updated revenue forecast is of great importance. The population in the East German states is declining and consequently also the transfers from the federal fiscal equalization scheme. Moreover, the transfer payments for East Germany since the German reunification will end 2019. All of these three facts lead to decreasing state revenues. The aim of the project is thus to estimate the extent of the decline and to formulate recommendations for the fiscal policy in the Free State of Saxony This project presents a continuation of the revenue forecast of the Free State of Saxony until 2025. For sustainable regional politics, more transparency in political decision-making, and especially in the current financial and economic crisis, a continuously updated revenue forecast is of great importance. The population in the East German states is declining and consequently also the transfers from the federal fiscal equalization scheme. Moreover, the transfer payments for East Germany since the German reunification will end 2019. All of these three facts lead to decreasing state revenues. The aim of the project is thus to estimate the extent of the decline and to formulate recommendations for the fiscal policy in the Free State of Saxony.
Keywords: E62; H60; 330; Steueraufkommen; Länderhaushalt; Öffentlicher Haushalt; Prognose; Sachsen; Finanzpolitik; Öffentliche Einnahmen; Haushaltskonsolidierung; Steuereinnahmen; Prognose; Sachsen